Adoption of Artificial Intelligence (AI) in Small and Medium Enterprise E-Commerce to Improve Marketing Performance - Rahmani, Shinta; Surya, Ade Permata; Rifqi, Muhammad; Setiawan, Sigit; Gunawan, Arien Arianti (Journal of Economics and Management Scienties, 2025)
This study investigates the key determinants influencing the adoption of Artificial Intelligence (AI) by Small and Medium Enterprises (SMEs) in the e-commerce sector and examines its impact on marketing performance. The research integrates the Technology–Organization–Environment (TOE) framework and the Technology Acceptance Model (TAM) to explain the relationships among technological readiness, organizational support, environmental pressure, perceived usefulness (PU), perceived ease of use (PEOU), and AI adoption level. A quantitative approach employing Partial Least Squares–Structural Equation Modeling (PLS-SEM) was conducted on 155 e-commerce SMEs operating in Jakarta, Indonesia. Empirical results reveal that technology, organization, and environment significantly affect perceived usefulness, which in turn strongly drives AI adoption. Perceived usefulness is identified as the most powerful determinant of adoption, whereas perceived ease of use exerts an indirect influence via usefulness perception. Furthermore, AI adoption has a positive and significant effect on marketing performance, particularly in enhancing digital campaign effectiveness, product innovation, and customer loyalty. The findings emphasize that internal readiness and external competitive pressures jointly foster AI-driven digital transformation within SMEs. The study provides both theoretical validation of the TOE–TAM integration and practical guidance for policymakers and business owners to design effective, ethical, and sustainable AI adoption strategies.